Bifidobacterium animalis Probio-M8 improves sarcopenia physical performance by mitigating creatine restrictions imposed by microbial metabolites - Zeng Zhang; Yajing Fang; Yangli He; Mohamed A. Farag; Min Zeng; Yukai Sun; Siqi Peng; Shuaiming Jiang; Xian Zhang; Kaining Chen; Meng Xu; Zhe Han; et al. (npj Biofilms and Microbiomes)
Abstract Sarcopenia is a major health challenge due to an aging population. Probiotics may improve muscle function through gut-muscle axis, but their efficacy and mechanisms in treating sarcopenia remain unclear. This study investigated the impact of Bifidobacterium animalis subsp. lactis Probio-M8 (Probio-M8) on old mice and sarcopenia patients. We analyzed 43 subjects, including gut microbiome, fecal metabolome, and serum metabolome, using a multi-omics approach to assess whether Probio-M8 can improve sarcopenia by modulating gut microbial metabolites. Probio-M8 significantly improved muscle function in aged mice and enhanced physical performance in sarcopenia patients. It reduced pathogenic gut species and increased beneficial metabolites such as indole-3-lactic acid, acetoacetic acid, and creatine. Mediating effect analyses revealed that Probio-M8 effectively reduced n-dodecanoyl-L-homoserine lactone level in gut concurrent with increased creatine circulation, to significantly enhance host physical properties. These findings provide new insights into probiotics as a potential treatment for sarcopenia by modulating gut microbiota metabolism.